Aparelho-obra: uma poética em arte e tecnologia - Pellegrin, Ricardo de (2023)
The present research reflects on the device-work as a concept capable of breaking with the programmability of technological devices, while also expanding the contexts of the artist's work in contemporary times by including the network (cyberspace). Based on the establishment of the device-work as a guiding concept, which allows the deepening and the continuation of personal poetics (2019-2023), a look is launched that updates the concepts of art and technology from artistic productions. Vilém Flusser's ideas, especially, support the understanding of device-work as a production that expands the understanding of device and promotes a critical approach with what is put in the relations between body, networks, subjects and technologies. Thus, the differential of the present research points to the potential of the device-works to produce a specific situation of engendering elements/materialities, constituting an inseparable whole, which involves technologies, the body-artist and the network (cyberspace) in an investigation process that reflects the panorama after the Covid-19 pandemic.